IMPLEMENTATION OF REWARDS IN JUNIOR HIGH SCHOOL STUDENTS IN VOCABULARY LEARNING - Siti Khomsah; Mobit Mobit; Iwan Ridwan (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The main focus of this research is the application of rewards in vocabulary learning. The purpose of this study was to determine the application of the reward method by the teacher in learning vocabulary. The researcher used a qualitative approach with a descriptive case study design. Data collection techniques used are observation, interviews, and documentation. To analyze the data, the researcher followed the steps described by Miles & Hubberman. These steps are: data reduction, data presentation, and drawing conclusions/verification. Through this investigation, the researcher found that when applying the reward method in vocabulary learning, the teacher did 6 stages. That is preparing the material, explaining the material, giving questions or games, giving rewards to students who take lessons well and answer questions correctly, providing opportunities to answer questions for students who are not focused, and adjusting the number of questions to the amount of the reward given.